The Relationship Between Spirituality and the Depression Level of the Elderly at the Nursing Home: A Study from Indonesia - Sairozi, Ali; Yusuf, Ah.; Ameliyah, Rizqi; Aris, Arival; Iswatun, (International Journal of Psychosocial Rehabilitation, 2020)
Religiousness is a vertical and horizontal two-dimensional concept. Ageing is not a disease but a continuation of the life process which is characterized by a decrease in the body's abilities. A psychological problem that is often experienced by the elderly is depression. The depression experienced by elderly people (84%) is caused y social isolation. The aim of this study was to analyze the relationship between spirituality and the level of depression in the elderly. This study used a correlational analytical method using a cross-sectional approach. The sampling method used was Simple Random Sampling with as many as 66 respondents. The data collection was done using a questionnaire and then for testing, we used the Spearmen rank test with a significance level of 0,05. The results showed that spirituality was most commonly in the moderate category (56 people: 84.8%) while for the most depression level, most were in the mild category (38 people: 57.6%). There was a significant relationship between spirituality and the level of depression of the elderly with a significance level of0.001